2019
DOI: 10.22605/rrh4971
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Rural Clinical School (RCS) program supports rural medical workforce: evidence from a cross-sectional study of 12 RCSs

Abstract: Committee approved the overall collation and analysis of the data from individual universities (approval 016190S). Each university gained approval from their institution's HREC to provide the deidentified data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(110 citation statements)
references
References 0 publications
2
102
0
6
Order By: Relevance
“…This study was conducted at three public health facilities in the Mangaung District (Free State Province, South Africa) that served high density, marginalised communities with rife unemployment and poverty [29]. HIV prevalence and TB mortality were estimated at 11 and 9% respectively in the in the district [29].…”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted at three public health facilities in the Mangaung District (Free State Province, South Africa) that served high density, marginalised communities with rife unemployment and poverty [29]. HIV prevalence and TB mortality were estimated at 11 and 9% respectively in the in the district [29].…”
Section: Settingmentioning
confidence: 99%
“…This study was conducted at three public health facilities in the Mangaung District (Free State Province, South Africa) that served high density, marginalised communities with rife unemployment and poverty [29]. HIV prevalence and TB mortality were estimated at 11 and 9% respectively in the in the district [29]. The incidence of drug sensitive TB among those commenced on TB treatment in the Free State Province (2017) was 429.8 per 100,000, compared with the national average of 378.6 per 100,000 [30].…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of adequate healthcare to rural populations is a global issue [1]. In Australia, despite government initiatives implemented in recent years, including increased funding to support medical rural medical training [2], medical workforce shortages and maldistribution between urban and rural locations are ongoing issues [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Rural Clinical Schools (RCS) program was implemented in 2000 and mandates that 25% of domestic medical students train rurally for at least one year of their clinical training [3]. Workforce outcomes for the RCSs program have been positive [4][5][6], and a recent study using combined data from multiple RCSs has showed that, independently of student background, RCS students had an increased chance of working rurally five years post-graduation [3]. Despite the program's success, evidence shows that at best, 50% of rural background RCS alumni end up in rural and regional areas [7].…”
Section: Introductionmentioning
confidence: 99%